An experimental system for measurements of Seebeck coefficient and electrical resistivity in bulk thermoelectric materials at high temperatures. (7th June 2019) - Wang, Jue; Zhao, Yu; Liao, Hao-Hsiang; Priya, Shashank; Huxtable, Scott T
Abstract: We describe the design, assembly, and operation of a novel instrument for measuring Seebeck coefficient and electrical resistivity of bulk thermoelectric materials of various shapes and sizes in the temperature range from 300 K to 600 K. The ability of the system to measure samples with a variety of shapes and sizes provides great flexibility in sample fabrication and preparation. The system is verified with Seebeck coefficient measurements on a standard material (SRM 3451) from NIST as well as a separate ZnO sample, a promising high temperature thermoelectric material, and the electrical resistivity is measured using the van der Pauw method. A variety of nickel-based samples with varying thickness are examined to validate the system and to demonstrate instrument precision and accuracy. The results indicate that this instrument is capable of rapid evaluation of the power factor for bulk thermoelectric materials without being limited to samples with specific shapes or dimensions.